CHRONIC ACTINIC CHEILITIS - GENERAL CONSIDERATIONS AND THE IMPORTANCE OF DERMATOSCOPY - Cristina Popa; Madalina Mocanu; Victor Vlad Costan; Stefan Vasile Toader; Mihaela Paula Toader (Romanian Dental Association for Education, 2022)
Chronic actinic cheilitis (AC) is a morbid condition with the potential for malignant transformation, predominantly affecting the vermilion of the lower lip in patients with a history of prolonged exposure to ultraviolet radiation. Classically, the diagnosis of actinic cheilitis is based on the visual clinical examination and the detailed anamnesis of the patient. In selected cases, tissue biopsy and histopathological analysis represent the gold standard for the diagnosis of certainty. Currently, digital dermatoscopy is an innovative, non-invasive in vivo technique which uses magnification lenses and a light source, enabling the visualization of structures in the deep epithelium and superficial chorion (either using polarized light, or a contact fluid to minimize light reflection off stratum corneum) at a magnification of 10 fold or more, depending on the device. It is useful in the primary assessment of actinic cheilitis, but also for dynamic monitoring of disease progression, early detection of progression to squamous cell carcinoma and evaluation of treatment effectiveness. Detailed epithelial and subepithelial structural aspects visible through digital dermatoscopy allow a rigorous selection of patients who need exposure to an invasive maneuver such as tissue biopsy.